(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The "Online Dial-A-Ride Problem (ODARP)" is discussed in this article and time constraints and demand specifics include a deadline to reach the time limit. If a proposal is not filed by its delivery date, it will be cancelled. For data limit, only data on the origin is presented whenever the application is received public. And until the basis of the request is met, the target of the server is not statistics. The purpose of the problem is to schedule a server movement so that its deadlines can be met for a determined figure of queries (or the extreme amount of goods). We examine competitively several deterministic strategies with various constraints on the problem. And in various cases this paper shows many lower limits on the competitiveness of any deterministic algorithm for the problem.